Assessing Phonological Profiles in Children and Adolescents With Down Syndrome: The Effect of Elicitation Methods - Diez-Itza, Eliseo; Vergara, Patricio; Barros, María; Miranda, Manuela; Martínez, Verónica (Frontiers in Psychology, 2021)
In the context of comparing linguistic profiles across neurodevelopmental disorders, Down syndrome (DS) has captured growing attention for its uneven profile. Although specific weaknesses in grammatical and phonological processing have been reported, research evidence on phonological development remains scarce, particularly beyond early childhood. The purpose of this study was to explore the phonological profiles of children and adolescents with Down syndrome. The profiles were based on the frequency and relative proportion of the processes observed by classes, and they were compared to those of typically developing preschool children of similar verbal age. A complementary goal was to assess the effect of two different methods of elicitation: a test of articulation and spontaneous speech sampling. Finally, intergroup and intragroup differences in full match percentages between three positions at syllable-level (complex onset, medial coda, and final coda) were assessed. The results of the present study confirmed that the frequency of phonological processes in children and adolescents with DS is atypically high and is above what is expected for lexical age and at the same level as grammatical age. Highly increased frequency of processes, consistent in all kinds of processes and positions at the syllable-level, and asynchronous with verbal age and mental age suggest atypical developmental trajectories of phonological development in the Down syndrome population.